Perencanaan Panduan Standar Keselamatan dan Kesehatan Kerja (K3) di Laboratorium Uji Tanah Politeknik Negeri Ambon - Hukom, Frando Simon; Mual, Billy Christ (Innovative: Journal Of Social Science Research, 2025)
The Soil Testing Laboratory of the Civil Engineering Department at Politeknik Negeri Ambon is a vital facility that supports learning and research activities in the field of soil mechanics. Various testing activities involving technical equipment and chemical substances present significant occupational hazards. Therefore, a well-planned Occupational Health and Safety (OHS) guideline is necessary to ensure a safe, orderly, and risk-minimized working environment. This study aims to develop an OHS guideline based on national regulations and international standards as a preventive measure against laboratory-related hazards. Key references include Law No. 1 of 1970, Ministerial Regulation No. PER.08/MEN/VII/2010 on Personal Protective Equipment (PPE), ISO 45001:2018, and Ministerial Regulation of Research, Technology, and Higher Education No. 55 of 2016. The resulting guideline is expected to serve as an operational reference that enhances safety, comfort, and productivity for all laboratory users within the Politeknik Negeri Ambon. Keywords: Hazards, Health and Safety, Laboratory, Risk